The presence of neighbours in informal supportive interactions is important for mental health in later life - Li, Yaya; Kabayama, Mai; Tseng, Winston; Kamide, Kei (Archives of gerontology and geriatrics, 2022)
•For people aged 65–74 in Japan, associations between social support and mental health varied in different social networks.•Supportive interactions with neighbours including giving and taking any types of support were related to a better mental health status.•Giving emotional support to kin members or friend was not related to mental health. Previous studies have shown the social support-mental health associations varied in different bonding social networks. However, a further study is needed to determine these network-specific associations for mutually supportive interaction in a wider social network include bridging relationship members. We conducted a self-reported questionnaire in Osaka, Japan. The study included 659 pre-old age participants (age 65–74 years) and 888 old age participants (age 75–89 years). SF-36v2 was used to measure mental health. We measured three types of social network members (kin, friends, or neighbours) and divided them into recipients or sources of emotional or instrumental social support. We performed multiple regressions to investigate which network member is beneficial in terms of the impact of social support on mental health. Only the neighbour social support was positively related with mental health in all subtypes. Associations were inconsistent amongst kin or friend social support subtypes. Positive associations were only found within the pre-old group. For pre-old people, only the presence of neighbours, not kin members, or friends, in social supportive interactions has consistently beneficial associations with mental health, regardless of the roles or functions. Accessibility of neighbour social support should be considered into community-based mental health promotion interventions along with the social network transformation in later life.